(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2017)
Construction projects currently present many errors and setbacks due to a lack of planning and control during the life cycle, so a virtual change beyond the 3d is necessary, with a multidimensional method where the real construction process is imitated by centralizing the information in a single model. The BIM methodology for the management of construction projects is an alternative that allows the reduction of uncertainty In this research a simple model of a one-story house will be developed as a case study, based on the seven dimensions (Idea, Sketch, 3D Visualization, Timing, Cost, Simulation of Energy Behavior and Sustainability and Life Cycle Management of a Construction Project which allows to have less uncertainty and help with decisions regarding the project.